Implementing the connectivity of natural areas in cities as an indicator in the City Biodiversity Index (CBI). (November 2018) - Deslauriers, Megan R.; Asgary, Adrienne; Nazarnia, Naghmeh; Jaeger, Jochen A.G.
Graphical abstract: Highlights: The improved method accounts for within-patch connectivity and barriers. The improved version is suitable for the CBI and has been implemented in it. It is useful for comparing planning scenarios to increase connectivity in cities. It can be applied for determining the impacts of urban development on connectivity. It can be applied easily by city planners around the world. Abstract: The City Biodiversity Index (CBI), or Singapore Index on Cities' Biodiversity, serves as a tool to monitor biodiversity in cities and was endorsed by the Convention on Biological Diversity in 2009. Indicator 2 of the CBI measures the connectivity of natural areas in cities. We propose an improved and straightforward method for measuring connectivity based on the effective mesh size metric to replace the previous method used in the CBI. The previous version did not account for intra-patch (within-patch) connectivity nor for major barriers. Our evaluation of the new version of Indicator 2 through its application to Montréal and Lisbon confirmed its reliability. In Montréal, natural areas have a total connectivity value of 581.7 ha, the majority of which exists between, rather than within, patches of natural area. Smaller patches (<15 ha) contribute significantly to overall connectivity, which may have implications for future conservation efforts. In Lisbon, connectivity (342 ha) is concentrated within patches. We also applied the improved Indicator 2 to a case study in southwestern Montréal, where a greenway network ("green infrastructure") has been proposed by a local community organization. We assessed the contribution of Meadowbrook Golf Course to connectivity in scenarios of the proposed greenway network and the effect that residential development would have. Not only would this development eliminate the golf course's current contribution to connectivity, but also its much greater potential contribution to connectivity in future scenarios. Restoring and establishing additional natural areas would significantly increase connectivity in the network. Our results demonstrate that the improved version of Indicator 2 is a suitable method in the CBI. It is equally useful for identifying options to increase the connectivity of natural areas within cities in the future and for determining the impacts of urban development on connectivity. More advanced methods for quantifying connectivity exist and may also be included in Part I of the CBI. However, they are often challenging to use and this frequently discourages city planners from including any indicator of connectivity in their biodiversity monitoring. The connectivity metric presented here overcomes this problem through its practicality in a wide range of planning structures while still generating meaningful results which may then inspire city planners to move towards using more advanced methods of measuring connectivity. We dedicate this paper to the memory of Bernice Goldsmith (1934–2014).